Recent Advances in Rare-Earth-Doped Nanoparticles for NIR-II Imaging and Cancer Theranostics - Yu, Zhenfeng; Eich, Christina; Cruz, Luis J. (Frontiers in Chemistry, 2020)
Fluorescence imaging in the second near infrared window (NIR-II, 1000-1700 nm) has been widely used in cancer diagnosis and treatment due to its high spatial resolution and deep tissue penetration depths. In this work, recent advances in rare-earth-doped nanoparticles (RENPs) - a novel kind of NIR-II nanoprobes - are presented. The main focus of this study is on the modification of RENPs and their applications in NIR-II in vitro and in vivo imaging and cancer theranostics. Finally, the perspectives and challenges of NIR-II RENPs are discussed.